FACTORS AFFECTING STOCK PRICE WITH DIVIDEND POLICY AS MODERATING VARIABLE - Jovena Lim; Sufiyati Sufiyati; Andreas Bambang Daryatno (Graduate Program of Universitas Tarumanagara, 2024)
The goal of this research was to gather empirical evidence on the effect of Firm size, Return On Equity, Leverage and Net Profit Margin on stock price, using Dividend Policy as moderating variable in consumer non cyclicals companies listed on the Indonesia Stock Exchange between 2020 and 2022. The method which is used to obtain the sample were purposive sampling and the data that met the criteria were 42 data from 18 companies which were processed using Statistical Package for the Social Science (SPSS) vers 26.0. Partially, Return On Equity has a significant and positive effect on stock price, Leverage (DER) and Net Profit Margin have a significant and negative effect on Stock Price, while Firm Size (Ln Asset) has no significant and positive effect on Stock Price. Dividend policy (DPR) unable to moderate the effect of Firm size, Return On Equity, Leverage and Net Profit Margin on Stock Price.